Exploring The Impact of Business Continuity Capabilities and Business Model Innovation on SMEs Performance in a Turbulent External Environment - Sanawiri, Brillyanes (Curtin University, 2024)
This study explores Indonesian SME resilience amid COVID-19, analyzing Business Continuity Capabilities (BCC) and Business Model Innovation (BMI) on performance. Utilizing interviews with 24 SMEs and a survey of 489, it identifies BCC drivers and their performance impact, underscoring BMI's mediating role. The findings offer insights for enhancing SME resilience in volatile environments, emphasizing the strategic integration of BCC and BMI for sustained performance.